Função pulmonar e teste de caminhada de seis minutos em indivíduos com doença falciforme - Ohara, Daniela Gonçalves (2014)
Background: Sickle Cell Disease (SCD) is characterized by a genetic mutation in beta hemoglobin chain, causing dysfunctions in the body, such as pulmonary function and functional capacity. Objective: To assessment the changes in pulmonary function and functional capacity in patients with sickle cell disease, as well as identify the relationship between these variables. Methods: Descriptive transversal study, exploratory and quantitative methodology, in which 21 subjects with sickle cell disease were evaluated (29±6 years), regarding sociodemographic, anthropometric, lung function (spirometry), respiratory (manovacuometer) and peripheral (Handgrip strength - HS) muscle strength and functional capacity (six-minute walk test - 6MWT). Proceeded to statistical analysis using the Shapiro-Wilk test, Paired t Student, Wilcoxon, Pearson and Spearman correlation (p<0.05). Results: It was observed changes in pulmonary function in 47.6% of subjects, 42.8% had a restrictive ventilatory pattern (RVP) and 4.8% had mixed ventilatory pattern. Maximal inspiratory pressure (MIP) presented predicted value below for women (obtained: 64±13cmH2O/ predicted: 93±2cmH2O) and maximum expiratory pressure (MEP), HS and distance walked during 6MWT had values below of predicted for men (obtained values: 103±27cmH2O; 39±7Kgf; 447±62m and predicted values: 143±5cmH2O; 45±1Kgf; 731±61m, respectively) and women (obtained values: 64±17cmH2O; 27±7Kgf; 405±71m and predicted values: 94±2cmH2O; 33±1Kgf; 683±30m, respectively). Positive correlations was observed of maximum voluntary ventilation (MVV) with MEP (r = 0.4; p=0.046) and body mass index (BMI) (r = 0.6; p=0.003); and HS with MIP (r = 0.7; p=0.001), MEP (r = 0.6; p=0.002), MVV (r = 0.5; p=0.015), distance walked in 6MWT (r = 0.4; p=0.038) and BMI (r=0.6; p=0.004). Conclusion: DF promoted changes in lung function and functional capacity, which predominated a RVP and reduced tolerance to physical exertion. In addition, these variables correlated with each other.